Transgenerational Glucose Intolerance of Tumor Necrosis Factor with Epigenetic Alteration in Rat Perirenal Adipose Tissue Induced by Intrauterine Hyperglycemia - Rina Su; Jie Yan; Huixia Yang (Journal of Diabetes Research)
Changes in DNA methylation may play a role in the genetic mechanism underlying glucose intolerance in the offspring of mothers with diabetes. Here, we established a rat model of moderate intrauterine hyperglycemia induced by streptozotocin to detect glucose and lipid metabolism of first-generation (F1) and second-generation (F2) offspring. Moderate intrauterine hyperglycemia induced high body weight in F1 and F2 offspring of diabetic mothers. F1 offspring had impaired glucose tolerance and abnormal insulin level. Additionally, F1 and F2 offspring that were exposed to intrauterine hyperglycemia had impaired insulin secretion from the islets. The tumor necrosis factor (Tnf) gene was upregulated in perirenal adipose tissue from F1 offspring and relatively increased in F2 offspring. Both F1 and F2 offspring showed similar hypomethylation level at the -1952 site of Tnf. We confirmed that DNA methylation occurs in offspring exposed to intrauterine hyperglycemia and that the DNA methylation is intergenerational and inherited.